2013
DOI: 10.3177/jnsv.59.37
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dietary Macronutrients on Induction of Hepatic Drug Metabolizing Enzymes by Coleus forskohlii Extract in Mice

Abstract: Summary From studies in mice, we have reported that Coleus forskohlii extract (CFE), a popular herbal weight-loss ingredient, markedly induced hepatic drug metabolizing enzymes, especially cytochrome P450 (CYP), and interacted with co-administered drugs. This study was designed to examine how the induction of drug metabolizing enzymes by CFE was influenced by different levels of macronutrients in the diet. Mice were fed a non-purified diet or semi-purified diet with and without CFE (0.3-0.5%) for 14-18 d, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Our laboratory previously reported that CYP, especially CYP3A, activity was induced more in mice fed a low protein diet (7% (w/w) casein) than in mice fed a control diet (20% (w/w) casein) [20][21][22]. A high-fat diet (P:F:C = 20:60:20) did not cause any changes in the hepatic expression of CYP3A, whereas regular chow (P:F:C = 26:13:61) increased CYP3A11 mRNA and CYP3A protein expression levels in the livers of mice more than the control diet (P:F:C = 20:10:70) [23].…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory previously reported that CYP, especially CYP3A, activity was induced more in mice fed a low protein diet (7% (w/w) casein) than in mice fed a control diet (20% (w/w) casein) [20][21][22]. A high-fat diet (P:F:C = 20:60:20) did not cause any changes in the hepatic expression of CYP3A, whereas regular chow (P:F:C = 26:13:61) increased CYP3A11 mRNA and CYP3A protein expression levels in the livers of mice more than the control diet (P:F:C = 20:10:70) [23].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that the induction of hepatic CYP and fatty liver by CFE in vivo can be easily evaluated by an increase in the liver/body weight ratio 16 . Therefore, the ability of target components in the materials to cause CYP and fatty liver was confirmed by dietary administration to mice and evaluation of increases in the liver/body weight ratio.…”
Section: Preparation Of Fractionated Samplesmentioning
confidence: 99%
“…The supernatant was centrifuged at 105,000 g at 4 for 60 min and used as microsomes to determine the total CYP content and CYP activities. The total CYP content was determined as previously described 16 . The activities of various CYP enzymes were determined using the P450-Glo TM CYP1A1 System Luciferin-CEE assay, CYP1A2 System Luciferin-1A2 assay, CYP2C9 System Luciferin-H assay, CYP3A4 System Luciferin PPXE assay and the NADPH Regeneration System, according to the manufacturer s instructions Promega .…”
Section: Assay Of Cyp Induction and Fatty Liver In Micementioning
confidence: 99%
“…Indeed, forskolin is a very effective activator of ACs 1 to 8 but not of AC9 [20,21]. CF has been reported to prove of value in the clinic for prevention of cancer metastasis [22].…”
Section: Introductionmentioning
confidence: 99%